Treating alcohol dependence with an abuse and misuse deterrent formulation of sodium oxybate: results of a randomised, double-blind, placebo-controlled study - Guiraud, Julien; Addolorato, Giovanni; Aubin, Henri-Jean; Batel, Philippe; de Bejczy, Andrea; Caputo, Fabio; Goudriaan, Anna E.; Gual, Antoni; Lesch, Otto; Maremmani, Icro; Perney, Pascal; Poulnais, Roch; et al. (European neuropsychopharmacology, 2021)
Sodium oxybate (SMO) has been approved in Italy and Austria for the maintenance of abstinence in alcohol dependent (AD) patients. Although SMO is well tolerated in AD patients, cases of abuse and misuse have been reported outside the therapeutic setting. Here we report on a phase IIb double-blind, randomized, placebo-controlled trial for the maintenance of abstinence in AD patients with a new abuse and misuse deterrent formulation of SMO. A total of 509 AD patients were randomized to 12 weeks of placebo or one of four SMO doses (0.75, 1.25, 1.75 or 2.25 g t.i.d.) followed by a one-week medication-free period. The primary endpoint was the percentage of days abstinent (PDA) at end of treatment. An unexpectedly high placebo response (mean 73%, median 92%) was observed. This probably compromised the demonstration of efficacy in the PDA, but several secondary endpoints showed statistically significant improvements. A post-hoc subgroup analysis based on baseline severity showed no improvements in the mild group, but statistically significant improvements in the severe group: PDA: mean difference +15%, Cohen's d = 0.42; abstinence: risk difference +18%, risk ratio = 2.22. No safety concerns were reported. Although the primary endpoint was not significant in the overall population, several secondary endpoints were significant in the intent-to-treat population and post-hoc results showed that treatment with SMO was associated with a significant improvement in severe AD patients which is consistent with previous findings. New trials are warranted that take baseline severity into consideration.